Protective immunity of recombinant LipL21 and I-LipL21 against Leptospira interrogans serovar Autumnalis N2 infection - Kumari, Anita; Premlatha, Mallela Martha; Raja, Veerapandian; Akino Mercy, Charles Solomon; Sumathi, Kalimuthusamy; Shariff, Malini; Natarajaseenivasan, Kalimuthusamy (The Journal of Infection in Developing Countries, 2018)
Introduction: Leptospirosis is a zoonotic disease caused by the spirochete of genus Leptospira with widespread distribution in tropical, subtropical and temperate zones. Leptospirosis is often confused with other febrile illnesses including jaundice, dengue, and malaria. Generally, the disease is often underdiagnosed or misdiagnosed. Though leptospirosis is curable with antibiotic treatment, the laboratory diagnosis of the disease is specialized and open to interpretation with multiple kits available to detect the different serological markers of Leptospira. Moreover, when leptospirosis is misdiagnosed, the disease can lead to multi-organ failure and may have fatal effects. There is a need for strategies to develop vaccines and prevent leptospirosis. In the present study, the immunogenic potential of leptospiral recombinant protein LipL21 (rLipL21) and its truncated form I-LipL21 (rI-LipL21) was evaluated. Methodology: The recombinant proteins were established in cyclophosphamide treated BALB/c mice model infected with L. interrogans serovar Autumnalis strain N2. Results: The vaccination study showed 66% and 83% survivability among mice immunized with rLipL21 and rI-LipL21 respectively and post-challenge with leptospiral strain N2 compared to control groups that showed 100% lethality. Additionally, a significant increase in antibody levels and cytokine levels (TNF-a, IFN-γ and IL-10) was observed evidencing a marked stimulation of both humoral and cell-mediated immune response in mice immunized with rLipL21/rI-LipL21 compared to whole cell leptospiral lysate (WCL). Conclusions: This study evidenced protective immunization against leptospirosis with rLipL21 and rI-LipL21 recombinant proteins and are potential candidates for the development of leptospiral vaccine.